Analysis Of Factors Influencing The Intention To Use Bank Syariah Indonesia Mobile Banking With Trust As Mediation - Mustika, Nindya; Puspita, Rosana Eri (Universitas Trunojoyo Madura, 2020)
This research is motivated by the problems that occur around students on Campus that they have a bank account in Bank Syariah Indonesia (BSI), but they have not mobile banking. This study has three independent variables, one dependent variable, and one mediating variable. This study investigates how perceived convenience, availability of Islamic features and risk perception are on intention-to-use BSI mobile banking with trust as the mediating variable. The grand theory of this study is the Technology Acceptance Model (TAM). The population is 3,650 students of the Islamic Business and Economics Faculty of IAIN Salatiga. The sample was taken by distributing questionnaires through purposive sampling technique. A criterion had been determined previously and was calculated using the Slovin formula so that the number of samples was 360 samples. The data was processed with IBM SPSS 23 and then analyzed using instrument tests, hypothesis testing, classical assumption tests, and path analysis. The first (partial) t-test shows that the perceived convenience variable and the availability of Islamic features have a significant positive effect on trustworthiness. In contrast, risk perception has a significant negative effect on trustworthiness. The second t-test results show the same results as the previous t-test for the intention-to-use BSI mobile banking. The path analysis results also show that the trust variable can mediate the perceived convenience, the availability of Islamic features, and the risk perception of the intention to use BSI mobile banking.